LIFE-FEED ENRICHMENT FOR LARVAL REARING OF YELLOWBAND CLOWNFISH (Premnas biaculeatus) - Ketut Maha Setiawati; Gunawan Gunawan (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2013)
The seeds of yellowband clownfish from hatchery has a pale skin colour and a yellow stripe became white colour.  The purposes of this research were to know the effects of life-feed enrichment on the growth of larva and the appearance of colors  yellowband clownfish. The treatments were the enrichment of rotifers and Artemia with commercial enrichment + Nannochloropsis (A), and without commercial enrichment as control, only Nannochloropsis (B). This research conducted for 15 days rearing. Larva rearings of yellowband clownfish fish with treatment A were resulted the total length at the end experiment was 7.72  ± 0.63 mm,  dan survival rate 52.6 ± 19.1 %.  The total length at treatment B was 7. 61  ± 0.43 mm and   survival rate 47.7 ± 24.2%.  Different enrichment of life-feed was not significant different effect for total length, survival rate and colour of seeds Keywords: life-feed, enrichment, growth, survival rate, colour, yellowband clownfish.